The experience of shared decision‐making for people with asthma: A systematic review and metasynthesis of qualitative studies. - Kang, Hui‐qi; Peng, Yueming; He, Yuanyuan; Yang, Xiufen; Su, Jin; Yang, Qiaohong; Luo, Weixiang (Health Expectations, 2024)
Objectives: To identify, describe and synthesise the views and experiences of adults living with asthma regarding shared decision‐making (SDM) in the existing qualitative literature Methods: We conducted a comprehensive search of 10 databases (list databases) from inception until September 2023. Screening was performed according to inclusion criteria. Tools from the Joanna Briggs lnstitute were utilised for the purposes of data extraction and synthesis in this study. The data extraction process in this study employed the Capability, Opportunity and Motivation Model of Behaviour (COM‐B model) as a framework, and a pragmatic meta‐aggregative approach was employed to synthesise the collected results. Results: Nineteen studies were included in the metasynthesis. Three synthesised themes were identified: the capability of people living with asthma, the opportunities of people living with asthma in SDM, and the motivation of the people living with asthma in SDM. Conclusions: We have identified specific factors influencing people living with asthma engaging in SDM. The findings of this study can serve as a basis for the implementation of SDM in people living with asthma and provide insights for the development of their SDM training programs. The ConQual score for the synthesised findings was rated as low. To enhance confidence, future studies should address dependability and credibility factors. Practice Implications: This review contemplates the implementation of SDM from the perspective of people living with asthma, with the aim of providing patient‐centred services for them. The results of this review can benefit the implementation of SDM and facilitate information sharing. It offers guidance for SDM skills training among adults living with asthma, fosters a better doctor–patient relationship and facilitates consensus in treatment decisions, thereby enabling personalised and tailored medical care. Patient or Public Contribution: Three nursing graduate students participated in the data extraction and integration process, with two students having extensive clinical experience that provided valuable insights for the integration.